What impact did the creation of Local Health Care Co-operatives have on indicators of practice resources and activity? - Sutton Matt; McLean Gary (BMC, 2008)
Abstract Background The creation of Local Health Care Cooperatives (LHCCs) in Scotland in 1999 was typical of attempts to encourage voluntary integration and co-operation between health care providers. One of the three stated objectives of their introduction was to tackle inequalities and improve access to care. Methods We used administrative data on all general practices in 1999 and 2003 to examine whether LHCCs had any measurable impact on six indicators of practice resources and activity. We compare three groups (participant, non-participant, and ineligible practices) through regression analysis of changes over time in group means and within-group inequality (measured using Gini coefficients). In addition, for participants we measure changes in the variation between and within LHCCs. Results Despite having similar registered populations to participants, non-participants had lower levels of resources at the start of the period and this differential widened over time. The changes over time in the activity indicators were similar across the three groups. There was little evidence that inequality between LHCC practices narrowed more than in the other two groups. Practices within LHCCs appear to be become more homogenous while variation increased between LHCCs. Conclusion The mixed messages from our examination of resources and activity indicators demonstrates that there are likely to be important lessons to be learned from the brief experiment with LHCCs. Clear objectives that are evaluated using a battery of simple performance indicators may help to ensure demonstrable change in future initiatives to foster integration and co-operation.